PENGARUH MOTIVASI BELAJAR TERHADAP HASIL BELAJAR PESERTA DIDIK MENGGUNAKAN PENDEKATAN DISCOVERY LEARNING - Ogot, Maria Yuliana; Wariani, Theresia; Tukan, Maria Benedikta (Fakultas Keguruan dan Ilmu Pendidikan, Universitas HKBP Nommensen, 2025)
Learning motivation is a drive or force that encourages an individual to take action to achieve a specific goal. The main objectives of this study, to determine the effectiveness of the Discovery Learning, to determine the level of students’ learning motivation, to find out the relationship between learning motivation and students’ learning outcomes, to determine the influence of learning motivation on students’ learning outcomes. This research was descriptive and associative in nature. The sample consists of 26 students from Grade XI MIA 2 at SMAN 1 Adonara Barat. Data collection techniques include observation, questionnaires, and tests. This study found that learning using the Discovery Learning approach is effective, indicated by: (a) teachers’ ability to manage the learning process is rated good, (b) mastery of learning outcomes for Core Competencies 3 and 4 is achieved, (c) mastery of indicators in Core Competencies 3 and 4 is also achieved. The learning motivation is categorized as strong. There is a relationship between learning motivation and learning outcomes. Learning motivation influences students’ learning outcomes.